2004
DOI: 10.1152/ajpendo.00056.2003
|View full text |Cite
|
Sign up to set email alerts
|

Increased systemic and adipose tissue cytokines in patients with HIV-associated lipodystrophy

Abstract: The lipodystrophy syndrome (adipose tissue redistribution and metabolic abnormalities) observed with highly active antiretroviral therapy (HAART) during human immunodeficiency virus (HIV) infection may be related to increased proinflammatory cytokine activity. We measured acute cytokine (TNF-α, IL-6, leptin), glycerol, and lactate secretion from abdominal subcutaneous adipose tissue (SAT), and systemic cytokine levels, in HIV-infected subjects with and without lipodystrophy (HIVL+ and HIVL–, respectively) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
95
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 71 publications
14
95
0
7
Order By: Relevance
“…We therefore concluded that the circulating evidence for inflammation in the lipodystrophic mice originated in the dystrophic fat. Importantly and consistent with our results, increased levels of expression of proinflammatory cytokines and macrophages (17,18) have been found in s.c. adipose tissue from humans with HIV-associated lipodystrophy, the most common form of lipodystrophy seen today. This data reinforces the relevance of the lipodystrophic mouse model used here to clinical practice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We therefore concluded that the circulating evidence for inflammation in the lipodystrophic mice originated in the dystrophic fat. Importantly and consistent with our results, increased levels of expression of proinflammatory cytokines and macrophages (17,18) have been found in s.c. adipose tissue from humans with HIV-associated lipodystrophy, the most common form of lipodystrophy seen today. This data reinforces the relevance of the lipodystrophic mouse model used here to clinical practice.…”
Section: Discussionsupporting
confidence: 92%
“…Inflammation has not been shown to contribute to the dysmetabolic consequences of lipodystrophy, although increases in the expression of proinflammatory cytokines and increased macrophage numbers have been found in the s.c. adipose tissue of patients with HIV-associated lipodystrophy (17,18). We therefore tested whether inflammation is associated with lipodystrophy and its metabolic consequences in aP2-nSREBP-1c transgenic (Tg) mice, an established model of the disease with characteristics that match many of those seen in humans (19).…”
mentioning
confidence: 99%
“…Thus, the low-adiponectin state may be the common defect in both obesity and lipodystrophy. However, increased plasma levels of various proinflammatory cytokines expressed by adipose tissue have also been observed in various groups of lipodystrophic subjects [7][8][9][10][11]. The aim of the present study was to investigate the interrelationships between the abnormalities of adiponectin and other adipokines, and to determine which defects are most closely predictive of the metabolic syndrome in a genetically and phenotypically well-characterised group of subjects with FPLD and unaffected controls.…”
Section: Introductionmentioning
confidence: 97%
“…High levels of expression of TNFa, and other cytokines such as interleukin-6 or interleukin-18 have been found in subcutaneous adipose tissue from HALS patients 14,64,85 together with similar increases in systemic levels of inflammatory cytokines such as TNFa, interleukins 1, 6, 8 and 18 and interferon-a. [86][87][88] Cytokine levels in blood correlated with viral load according to some studies. 88 Moreover, there is evidence of macrophage infiltration including the presence of lipogranulomas in subcutaneous adipose tissue in HALS.…”
Section: The Paradox Of the Common Inflammation Status In Adipose Tismentioning
confidence: 97%